The relationship of knowledge about the impact of early marriage on pregnancy and delivery With adolescent women's attitudes towards Early marriage in the working area of Tuntungan health center, pancur Batu district in 2021 - Aprilita Sitepu; Desriati Sinaga; Natalia Reni Pangaribuan (Science Midwifery, 2021)
Marriage is an event in which a pair of prospective husband and wife are formally met in front of a certain religious leader, witnesses and a number of attendees to then be officially ratified as husband and wife with certain ceremonies and rituals (Kartono, 2018). The purpose of the study was to analyze the relationship between knowledge about the impact of early marriage on pregnancy and adolescent attitudes towards early marriage in the Tuntungan Health Center Work Area, Pancur Batu District in 2021. The population in this study were all female students in the Tuntungan Public Health Center working area, Pancur Batu District in 2021. A total of 104 people. The sample in this study was all female students in the working area of ​​the Tuntungan Health Center, Pancur Batu District in 2021 as many as 104 people. The results of the study based on knowledge, most of the respondents had less knowledge as many as 99 respondents (95.2%). Based on the attitude of most of the respondents have a bad attitude as many as 97 respondents (93.3%). Conclusion Most of the respondents have low knowledge due to the lack of information received about the impact of early marriage on pregnancy and childbirth. Because the more information received, the more knowledge gained. The education of the respondent's parents also has an educated elementary school as many as 72 respondents from 104 respondents. The higher a person's education, the person will tend to get more information. It can also affect knowledge about the impact of marriage on pregnancy and childbirth.